Tunneling construction technology of shafts and cross-passages under strictly controlling deformation of the existing railway - Liu, Liu; Xu, Gongwen; Li, Rongxian; Fang, Zhichun; Chen, Hongwen; Wu, Siqi; Xu, Wenbo; Han, Bing; Ma, Chaoyi; Shen, Qian (Frontiers in Earth Science, 2023)
Underground construction will have more or less adverse effects on adjacent existing buildings with more and more existing buildings above ground. However, this situation has only been reported by a small number of researchers. In view of this, this paper takes the existing airport line shaft and horizontal passage project in the western suburb of Beijing Metro Line 12 as the background to study the impact of the construction of subway station and shaft passage on the adjacent existing railway. Based on the theory of tunnel-foundation-sub grade interaction, under the action of pavement load, the effects of different parameters (the distance between the surface measuring point and the middle line of the transverse passage and the sub step of construction loading sup step) on the surface settlement and track deformation of the shaft and cross-passage through the existing railway are studied by numerical analysis method. The calculation results show that the construction method of shaft and cross passage is reasonable. The comprehensive reinforcement measures of sub grade, rail and hole are effective, effectively controlling the deformation of sub grade and rail within the standard value (surface settlement ≤ 60 mm, rail deformation ≤ 6 mm). In addition, the numerical simulation data can better represent the actual situation as a whole.